A Brief Review on Engaging and Interactive Learning for Children: Exploring the Potential of Metaverse-Based Oral Health Promotion - Vini Mehta; Ankita Mathur; Himanshu Chaurasia; Vishnu Teju Obulareddy; Cesare D'Amico; Luca Fiorillo (Hindawi Limited, 2024)
The importance of oral health for overall health makes it critical to establish proper oral hygiene practices in children early on. The traditional approaches to teaching children about dental health may not be successful since they may not be able to keep their interest. Metaverse technology offers a promising alternative, allowing for the design of engaging and immersive worlds that can effectively educate children about oral health. Despite the growing interest in the use of metaverse technology in healthcare, there is a lack of comprehensive reviews on its potential for oral health promotion in children. This review aims to fill this gap by providing an overview of the current state of metaverse-based oral health promotion for children, discussing its benefits and challenges, and highlighting its potential for improving children's oral health. By conducting this review, the authors hope to provide new information on the potential of metaverse-based oral health promotion for children and to contribute to the ongoing discussion on the use of metaverse technology in healthcare. This review may also provide valuable insights for dental organizations and practitioners interested in using metaverse technology to promote oral health and healthy living among children.